Studi Mikroskopis Batuan dari Sungai Aranio Kalimantan Selatan dengan Metode Petrografi - Janah, Raihul; Wianto, Totok; Sudarningsih, Sudarningsih (Jurnal Fisika FLUX, 2010)
Done observation petrography to detect colour, structure, texture,mineral composition and rock classification. Rock sample that taken from AranioRiver, South Kalimantan as much as 4 (four) samples, made to be thin slicemeasures ï± 6 cm x 3 cm x 3 mm use rock clipper dan rock slice refiner. Rockthin slice is analyzed by means of polarization microscope. Analysis resultpetrography mentions that any sample amphibolites rocks (hornblende sekis)that belong in faces metamorphic rock. Two samples among others texturedgrano-lepidoblastic and poikiloblastic, while two textured another samples granolepidoblasticand textured lepidoblastic and poikiloblastic. Crystal size from rocksamples amphibolites revolve from 0,40 mm until 0,80 mm, has lineationstructure (crystal instruction) and clear colour up to muddy greenness. This rockprincipal mineral composition consists of amphibole (34 â 60 %), quartz (22 â 44%), plagioclase (4 â 14 %), biotitic (1 %), epidotic (4 â 10 %), garnet (1 â 2 %),cyanide (1 â 6 %) and pyroxene (2 %); addition mineral consists of oxide iron (1â 3 %) and calcite (6%).